Effects of Dietary Salt-Based Minerals and Phosphorus Supplements on Mean Body Weight, Survival Rate and Feed Conversion Ratio of White Shrimp Reared In Brackish Water - Amir, Nizar; Efendy, Makhfud; Hidayat, Agriananta Fahmi (Rekayasa, 2021)
This study aimed to examine the impact of dietary salt-based mineral and phosphorus supplements on mean body weight, survival rate, and feed conversion ratio of Litopenaeus vannamei (white shrimp) reared in brackish water. The experiment was performed randomized design with three replicates in each treatment used twelve 40 L rectangular polymethyl methacrylate containers reared 45 days. The four treatments in this study were based on the concentration of salt-based mineral and phosphorus supplements (control or 0 ppm, one ppm, two ppm, and three ppm) in dietary of white shrimp. The results showed that using salt-based mineral and phosphorus supplements in dietary of white shrimp positively impacts mean body weight, survival rate, and feed conversion ratio. Increasing the concentration of salt-based mineral and phosphorus supplements increased mean body weight and survival rate and reduced feed conversion ratio of white shrimp. The mean body weight, survival rate, and feed conversion ratio of white shrimp were achieved with three ppm of dietary salt-based mineral, and phosphorus supplements reared 45 days was 5.98 gr, 88.57%, and 1.45, respectively.